Polyvinyl alcohol film, method for producing the same, and optical film using the same

By placing the PVA film in 0.2 wt% aqueous boric acid solution to ensure uniformity of its melting point and crystallization temperature, the color unevenness of the PVA film is solved and the yield of the optical film is improved.

CN115073777BActive Publication Date: 2025-02-07CHANG CHUN PETROCHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110346899.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-10
Filing Date
2021-03-31
Publication Date
2025-02-07
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

In the prior art, when using polyvinyl alcohol (PVA) film to prepare large-size optical films, problems such as uneven dyeing, color blocks and color spots are often encountered, which increases the difficulty of preparation.

Method used

By placing the PVA film in 0.2 wt% aqueous boric acid solution, the melting point (Tm) > 210°C, the melting point difference (ΔTm) < 3.2°C, and the crystallization temperature (Tc) < 153.5°C, the crystallization temperature difference is shown in the DSC measurement. (ΔTc) < 3.85°C for color uniformity.

Benefits of technology

This treatment method effectively solves the problem of uneven color of PVA film when preparing optical films, improves the yield of optical films, and is especially suitable for the manufacture of large-size polarizing films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115073777B_ABST
    Figure CN115073777B_ABST
Patent Text Reader

Abstract

The present invention relates to a polyvinyl alcohol film, a method for manufacturing the same and an optical film using the same. After being treated with boric acid, the polyvinyl alcohol film has a melting point (Tm) greater than 210°C, and a melting point difference ΔTm between any two locations of the film is less than 3.2°C. The polyvinyl alcohol film having the above characteristics has uniform color after stretching and dyeing, and does not produce uneven dyeing problems such as color blocks or color spots, thereby improving the defects of the polyvinyl alcohol film in manufacturing the optical film and improving the yield of the optical film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polyvinyl alcohol (PVA) film which can be used as an optical film, in particular a polarizing film. Background Art

[0002] Polyvinyl alcohol (PVA) film is a hydrophilic polymer with properties such as transparency, mechanical strength, water solubility, and good processability. It has been widely used in packaging materials or optical films for electronic products, especially polarizing films.

[0003] When manufacturing polarizing film, the PVA film is placed in a boric acid solution for stretching and dyeing. The dye molecules diffuse into the PVA molecules of the PVA film and arrange themselves regularly, so that the polarizing film can absorb the light components parallel to its arrangement direction, and allow the light components in the vertical direction to pass through and produce polarizing characteristics.

[0004] A good polarizing film has the characteristics of uniform color, few color spots and no wrinkles, and can provide better optical properties. In order to improve the optical properties of polarizing films, the existing technology will change the structure of polyvinyl alcohol or add functional groups (such as cationic groups) to change the viscosity or saponification degree, thereby improving the optical properties. Summary of the invention

[0005] Although the known technology has provided a method for improving the optical properties of PVA film when it is made into a polarizing film, when PVA film is used in the prior art to prepare large-sized optical films, uneven dyeing, color blocks and spots, or uneven color when stretched often occur, increasing the difficulty of preparing the optical film.

[0006] Therefore, in order to solve the above problems, the purpose of the present invention is to provide a polyvinyl alcohol (PVA) film, which, after being treated with 0.2wt% boric acid, has a melting point (Tm)>210°C measured by a differential scanning calorimetry (DSC), and the melting point difference (ΔTm) between any two points of the PVA film is <3.2°C.

[0007] In a preferred embodiment, the PVA film treated with 0.2 wt % boric acid aqueous solution has a crystallization temperature (T c )<153.5℃.

[0008] In a preferred embodiment, the crystallization temperature difference (ΔT c )<3.85℃.

[0009] In a preferred embodiment, the PVA film has a standard deviation of hysteresis <3 nm.

[0010] In a preferred embodiment, 0.12 g of the PVA film is treated with a 0.2 wt % boric acid aqueous solution and dissolved in water, and the boron content of the aqueous solution is 16 to 19 ppm.

[0011] Another object of the present invention is to provide an optical film, which is made from the PVA film of the present invention.

[0012] In a preferred embodiment, the optical film is a polarizing film.

[0013] In a preferred embodiment, the polarizing film has a polarization brightness>99.8.

[0014] Another object of the present invention is to provide a method for manufacturing the PVA film of the present invention, comprising: (a) stirring a polyvinyl alcohol-based resin at a heating rate of 4 to 20°C / hour, and after the dissolution temperature reaches >100°C, maintaining the temperature for 2 to 4 hours, and reversing the stirring direction at least twice per hour to form a polyvinyl alcohol casting solution; (b) casting the casting solution onto a casting roller; and (c) forming the PVA film after drying.

[0015] In a preferred embodiment, the rotation speed of the casting drum is 3-7 m / min.

[0016] In a preferred embodiment, the drying in step (c) is carried out by a hot roller or a floating dryer.

[0017] In a preferred embodiment, the maximum / minimum air flow rate received by the membrane along the width direction in the floating dryer is ≤3.0.

[0018] In a preferred embodiment, the polyvinyl alcohol casting solution further includes a plasticizer, and the plasticizer is 3 to 30 parts by weight relative to 100 parts by weight of the polyvinyl alcohol-based resin.

[0019] In a preferred embodiment, the polyvinyl alcohol casting solution contains the polyvinyl alcohol-based resin in an amount of 10 to 60% by weight.

[0020] In a preferred embodiment, the degree of polymerization of the polyvinyl alcohol-based resin is between 800 and 10,000.

[0021] Compared with the known technology, the PVA film of the present invention has uniform color after dyeing, and does not produce color unevenness problems such as color blocks or spots, which effectively improves the defects of PVA in manufacturing optical films and improves the yield of manufacturing optical films, especially for manufacturing large-size polarizing films. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1Schematic diagram of cutting three 10cm*10cm test pieces from PVA film on the left, middle and right. DETAILED DESCRIPTION

[0023] The following embodiments should not be considered to unduly limit the present invention. Those skilled in the art may modify and alter the embodiments discussed herein without departing from the spirit or scope of the present invention, and still fall within the scope of the present invention.

[0024] The terms "a", "an" and "a" as used herein represent that there is one or more than one (ie, at least one) of the grammatical object of the present invention.

[0025] In the present invention, the MD is the machine direction, i.e. the longitudinal direction of the PVA film; and the TD is the transverse direction, i.e. the transverse direction of the PVA film.

[0026] The method for manufacturing a polyvinyl alcohol (PVA) film of the present invention comprises the following steps: preparing a polyvinyl alcohol casting solution, casting the polyvinyl alcohol casting solution onto a casting roller, and forming a polyvinyl alcohol polymer film after drying.

[0027] Specifically, the method for manufacturing the PVA film includes the following steps: in a dissolution tank, dissolving the polyvinyl alcohol resin in a solution (e.g., water) to form the polyvinyl alcohol casting solution; optionally filtering the polyvinyl alcohol casting solution using a filter; then, using a gear pump and a coater (e.g., a T-die coater) to cast the polyvinyl alcohol casting solution onto a casting roller; finally, peeling off the PVA film formed on the roller, and obtaining the PVA film through a series of heat treatments such as hot rollers and / or drying.

[0028] To prepare the polyvinyl alcohol casting solution, the polyvinyl alcohol resin is dissolved in a dissolving tank, and the dissolving temperature in the dissolving tank is >100°C, preferably >110°C, and more preferably >120°C, for example 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C or 140°C, and the present invention is not limited thereto. The dissolving tank is preferably heated at a rate of 4 to 20°C per hour, preferably 5 to 15°C, more preferably 6 to 9°C, specifically 4.0°C / hr, 5.0°C / hr, 6.0°C / hr, 7.0°C / hr, 8.0°C / hr, 9.0°C / hr, 10°C / hr, 11°C / hr, 12°C / hr, 13°C / hr, 14°C / hr, 15°C / hr, 16°C / hr, 17°C / hr, 18°C / hr, 19°C / hr or 20°C / hr, etc. If the heating rate is too fast, the polyvinyl alcohol resin is prone to agglomeration, resulting in incomplete dissolution. After heating to the desired dissolving temperature, the polyvinyl alcohol casting solution is continuously stirred for 2 to 4 hours, preferably 3 hours, and the stirring direction is changed at least 2 times, preferably 3 times, every hour, for example, rotating clockwise for 20 minutes and then changing to counterclockwise for 20 minutes. Reversing the direction during the stirring process can increase the dissolution effect and prevent clusters from remaining in the polyvinyl alcohol casting solution.

[0029] The polyvinyl alcohol casting solution is prepared, and the content of the polyvinyl alcohol resin is 10 to 60% by weight, preferably 15 to 40% by weight, and more preferably 20 to 30% by weight, specifically 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60% by weight. If the content of the polyvinyl alcohol resin is insufficient, the viscosity of the polyvinyl alcohol casting solution will be too low, and the drying load will be too large, resulting in poor film-forming efficiency in preparing the PVA film. On the contrary, if the content of the polyvinyl alcohol resin is too high, the polyvinyl alcohol resin is not easy to dissolve, and clusters are likely to remain, resulting in deterioration of the phase difference uniformity of the PVA film and affecting the dyeing uniformity of the subsequent process.

[0030] The above-mentioned polyvinyl alcohol resin is obtained by polymerizing vinyl ester resin monomers to form polyvinyl ester resins, and then performing saponification reaction; wherein the vinyl ester resin monomers include vinyl esters such as vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl valerate or vinyl octanoate, and the present invention is not limited thereto, and vinyl acetate is preferred. In addition, copolymers formed by copolymerization of olefin compounds or acrylate derivatives with the above-mentioned vinyl ester resin monomers can also be used; the olefin compounds include ethylene, propylene or butene, etc., and the present invention is not limited thereto. The acrylate derivatives include acrylic acid, methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate or n-butyl acrylate, etc., and the present invention is not limited thereto.

[0031] The saponification degree of the polyvinyl alcohol resin is 90% or more, preferably 99% or more, to obtain better optical properties, such as 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 99.1, 99.2, 99.3, 99.4, 99.5, 99.6, 99.7, 99.8, 99.9%, etc. The degree of polymerization of the polyvinyl alcohol is between 800 and 10,000, and preferably between 2,200 and 10,000, such as 800, 900, 1,000, 2,000, 3,000, 4,000, 5,000, 6,000, 7,000, 8,000, 9,000, 10,000, etc. A degree of polymerization higher than 800 has better processing properties, but a degree of polymerization higher than 10,000 is not conducive to dissolution.

[0032] In addition to the polyvinyl alcohol resin, the casting solution may also contain a plasticizer to improve the processability of the film. The plasticizer that can be used includes polyols, such as ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol or glycerol, etc., and the present invention is not limited thereto. Preferably, ethylene glycol and glycerol are used. The amount of the plasticizer added is usually between 3 and 30 parts by weight relative to 100 parts by weight of the polyvinyl alcohol resin, preferably between 7 and 20 parts by weight, specifically, for example, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 parts by weight, etc. If the content of the plasticizer is insufficient, the formed PVA film is prone to crystallization and affects the dyeing performance of subsequent processing. On the contrary, if the plasticizer content is too high, the mechanical properties of the PVA film will be damaged.

[0033] The equipment used in the manufacturing method of the PVA film includes a dissolving tank, a filter, a coating machine, and a conveying pipeline connected from the dissolving tank to the coating machine. In a preferred state, the equipment is covered with a heat preservation device, which can be a metal electric heating wire or a jacket containing a liquid, such as oil or water. By heating the metal wire or the liquid in the jacket, the equipment is kept in a heat preservation state with uniform heating, especially the surface of the equipment and the pipeline, to prevent the equipment or the pipeline from losing the surface temperature and causing the polyvinyl alcohol in the polyvinyl alcohol casting solution to form gel or clusters. In addition, the heat preservation temperature should not be too high, otherwise it will cause part of the polyvinyl alcohol casting solution to dehydrate or gel, forming a brown or black gel, which will affect the surface quality and uniformity of the PVA film after subsequent coating and film formation. The insulation temperature of the polyvinyl alcohol casting solution at the coating molding location is 80-120°C, preferably 90-110°C, more preferably 90-100°C, specifically 80, 85, 90, 95, 100, 105, 110, 115, 120°C, etc.

[0034] When the polyvinyl alcohol casting solution is cast onto the casting drum, the rotation speed of the casting drum is about 3 to 7 m / min, preferably 4 to 6 m / min. When the drum speed is too slow, the casting solution is over-dried, and there is a tendency for phase difference and uneven melting point distribution. On the contrary, when the drum speed is too fast, the casting solution is not dried sufficiently and the peelability is reduced. In addition, in a preferred embodiment, the temperature of the drum is set at 85 to 90°C, for example 85, 86, 88, 87, 88, 89, 90°C, etc. If the drum temperature is too high, the casting solution on the drum is prone to bubbling.

[0035] After the PVA film initially formed on the casting roller is peeled off from the roller, it is dried to form a PVA film. The drying process can be carried out on a hot roller or on a floating dryer. The number of the hot rollers and floating dryers is not particularly limited and can be adjusted as needed. However, in a preferred embodiment, the maximum / minimum temperature ratio of the drying compartment (i.e., the oven) is 2.0 to 2.4; when the compartment temperature ratio is too large, it is easy to cause uneven crystallinity, so that the PVA film will react unevenly with boric acid when used to make optical films. In addition, the temperature difference between adjacent compartments is preferably below 65°C, more preferably below 60°C, and optimally 50°C. When the temperature difference between adjacent compartments is too large, it is easy to cause uneven distribution of phase differences. In addition, there is no specific restriction on the amount of airflow received by the PVA film formed along the width direction (i.e., perpendicular to the machine direction) in the floating dryer, but the maximum / minimum airflow ratio must be controlled below 3.0, such as 0, 0.5, 1.0, 1.5, 2.0, 2.5 or 3.0. Since places with large air volume are easy to take away moisture and have a high degree of drying, this airflow ratio range can control the air volume contacted by each position of the PVA film to be the same, so as to achieve uniform drying. In addition, if the airflow ratio is too large, the PVA film will react unevenly with boric acid and have uneven phase differences when used to make optical films.

[0036] The "treatment with 0.2 wt% boric acid aqueous solution" of the present invention is (a) placing about 0.1 g of PVA film in 20 g of pure water, so that the PVA film is completely immersed below the liquid level of the pure water, and stirring at a stirring speed of 250 rpm for 1 hour; (b) taking the PVA film out of the pure water and placing it in a 0.2 wt% boric acid aqueous solution, and then standing for 1.0 hour; and (c) after taking the PVA film out of the 0.2 wt% boric acid aqueous solution, placing the PVA film in a closed container and standing for 16.0 hours to complete the boric acid treatment. In the present invention, a relatively low boric acid concentration is used, because if a higher concentration of boric acid is used, the region in the PVA film that is originally difficult to react will also become reactive due to the high concentration of boric acid, so it is difficult to observe the uniformity of the film.

[0037] The PVA film of the present invention, after being treated with boric acid, has a melting point (Tm) measured by a differential scanning calorimetry (DSC) > 210°C, and a melting point difference (ΔTm) of any two points of the PVA film < 3.2°C. For example, the melting point (Tm) is 211°C, 212°C, 215°C, 220°C, 225°C or 230°C, etc., and the present invention is not limited thereto; the ΔTm of any two points of the PVA film is, for example, 1°C, 1.5°C, 2°C, 2.5°C, 3°C or 3.1°C, etc., and the present invention is not limited thereto.

[0038] When manufacturing optical films, PVA films are stretched and dyed. Taking polarizing films as an example, since the polarizing film manufacturing process uses I3 - 、I5 - When the boric acid aqueous solution containing iodine ions is used to dye the PVA film, the boric acid can cross-link with the amorphous region of the PVA to fix the iodine ions and prevent the iodine ions from dissolving out. However, after the PVA molecules are cross-linked with the boric acid, the crystallinity will decrease and the melting point will also decrease. When the crystallinity is unevenly distributed, the PVA film will react unevenly with the boric acid, resulting in I3 - 、I5 - Uneven fixation of iodine ions leads to uneven color. Therefore, the present invention treats the PVA film with boric acid to simulate the boric acid immersion used in the polarizer process, and uses a lower boric acid concentration (0.2wt% in this article) to more easily analyze the differences in different positions, and the melting point (Tm) measured by differential scanning calorimetry (DSC) is >210°C, and the ΔTm of any two points of the PVA film is <3.2°C. The PVA film has suitable and uniform crystallinity, and when stretched and dyed, a polarizing film with uniform color can be obtained. The PVA film of the present invention can also be used to prepare other stretched and dyed optical films, not limited to polarizing films.

[0039] Furthermore, the PVA film treated with boric acid has a crystallization temperature (T c )<153.5°C. For example, the crystallization temperature (T c ) is 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 150°C or 155°C, etc., and the present invention is not limited thereto.

[0040] Furthermore, the ΔT between any two points of the PVA film treated with boric acid c <3.85°C. For example, the ΔT at any two points of the PVA film treated with boric acid isc It is 0°C, 0.5°C, 1°C, 1.5°C, 2°C, 2.5°C, 3°C or 3.19°C, etc., and the present invention is not limited thereto.

[0041] In the present invention, the method steps of DSC measurement include: Figure 1 As shown, one of the MD positions of the PVA film is cut into three 10cm*10cm test pieces along the TD direction within 40 cm from the end in the TD direction, namely the left, middle and right test pieces. Next, 0.1g of the PVA film is weighed on each test piece, placed in a glass bottle and 20g of pure water is added so that the PVA film is completely below the pure water level, a stirring stone is added, the stirring speed is 250rpm, and stirring is performed at room temperature for 1.0 hour. Subsequently, the pure water in the glass bottle is poured out, 20g of 0.2wt% boric acid aqueous solution is added, and after standing for 1.0 hour, the boric acid aqueous solution is poured out so that the boric acid-treated PVA film is sealed in the bottle and allowed to stand for 16.0 hours. Finally, the PVA film treated with boric acid was taken out, spread on an iron plate, and dried at 105°C for 1.0 h. Then, the PVA film treated with boric acid was taken out and analyzed by DSC. The DSC experimental temperature range was 30°C to 250°C. The temperature was maintained at 30°C and 250°C for 1 minute each. The melting point (T m ), the crystallization temperature during the first cooling (T c ), the glass transition temperature during the second heating (T g ). The DSC measuring instrument can be a common DSC instrument, such as DSC:TA Instruments DSC 25.

[0042] Further, the PVA film of the present invention has a standard deviation of hysteresis <3nm. For example, the standard deviation of hysteresis of the PVA film is 0nm, 0.5nm, 1.0nm, 1.5nm, 2.0nm, 2.5nm or 2.9nm, etc., and the present invention is not limited thereto.

[0043] The retardation mentioned in the present invention refers to the amount of phase change of the incident polarized light when the light passes through the film, that is, the amount of phase delay, and the unit is nm; the uniformity of the retardation value involves the uniformity of molecular orientation and thickness, which has a great impact on the subsequent optical film manufacturing process. Figure 1 As shown, the measurement of hysteresis is to cut out three 10cm*10cm test pieces on the left, middle and right sides of one MD position of the PVA film treated with boric acid within 40cm from the end in the TD direction for measurement. The hysteresis values ​​and statistical data (maximum value, standard deviation, etc.) of all points in the surface can be obtained.

[0044] Furthermore, after 0.12g of the PVA film of the present invention is treated with a 0.2wt% boric acid aqueous solution and dissolved in water, the boron content of the aqueous solution is 16 to 19ppm. Specific examples include 16ppm, 16.5ppm, 17ppm, 17.5ppm, 18ppm, 18.5ppm or 19ppm, and the present invention is not limited thereto. If the boron content is lower than the above, the color fixation ability of the PVA film during subsequent dyeing is insufficient and poor; if the boron content is higher than the above, the degree of crosslinking between boric acid and PVA is too high, which is not conducive to the subsequent stretching manufacturing process and poor.

[0045] In the present invention, the method for measuring the boron content comprises the following steps: taking out the PVA film treated with boric acid, passing it through pure water, putting it into a 30 ml glass sampling bottle, adding 20 g of pure water, and analyzing the boron concentration in the solution by ICP-OES after fully dissolving it.

[0046] The optical film of the present invention is made of the PVA film of the present invention. The optical film includes a polarizing film, an anti-blue light film, a filter, etc., but the present invention is not limited thereto. Preferably, the optical film is a polarizing film, and the polarizing film has a polarization brightness>99.8. Specific embodiments

[0048] Hereinafter, the present invention will be further described with detailed description and examples. However, it should be understood that these examples are only used to help the present invention to be more easily understood and are not used to limit the scope of the present invention.

[0049] Examples 1 to 4

[0050] Manufacturing PVA film: Polyvinyl alcohol resins with melting points (Tm) of 233.21°C, 233.24°C, 233.01°C and 233.08°C were used as main components of the polyvinyl alcohol casting solution, respectively, and the manufacturing method of the PVA film of the present invention was used to prepare the PVA films of Examples 1 to 4. The operating conditions of the manufacturing method are shown in Table 1.

[0051] Comparative Examples 1 to 3

[0052] Preparation of PVA film: Polyvinyl alcohol resins with melting points (Tm) of 233.15°C and 233.17°C were used as main components of the polyvinyl alcohol casting solution, respectively. The same method for preparing the PVA film of the present invention was used but the operating conditions were different to prepare PVA films of Comparative Examples 1 to 3. The operating conditions of the manufacturing method are shown in Table 1.

[0053] Experimental example

[0054] Property analysis of PVA films: The standard deviation of hysteresis was measured for the PVA films of Examples 1 to 4 and Comparative Examples 1 to 3, and the melting point (Tm), melting point difference (ΔTm), crystallization temperature (Tm) and crystallization temperature (Tm) were measured after further treatment with 0.2 wt % boric acid aqueous solution. c ), crystallization temperature difference (ΔT c ), boron content, the measurement results are shown in Table 2.

[0055] Preparation of polarizing film: The PVA films of Examples 1 to 4 and Comparative Examples 1 to 3 were immersed in water at about 30°C respectively to swell them, and then the first uniaxial stretching was performed, and the film was stretched in the MD direction. The length after stretching was 2.0 times the original length of the PVA film. Then, the PVA film after the first stretching was immersed in a 30°C aqueous solution containing 0.03% by mass of iodine and 3% by mass of potassium iodide, and the second uniaxial stretching was performed, and the film was stretched in the MD direction. The length after stretching was 3.3 times the original length of the PVA film. Immediately afterwards, the PVA film after the second stretching was immersed in a 30°C aqueous solution containing 3% by mass of potassium iodide and 3% by mass of boric acid, and the third uniaxial stretching was performed, and the film was stretched in the MD direction. The length after stretching was 3.6 times the original length. Subsequently, the PVA film after the third stretching was immersed in a 60°C aqueous solution containing 5% by mass of potassium iodide and 4% by mass of boric acid, and the fourth uniaxial stretching was performed, and the film was stretched in the MD direction. The length after stretching was 6.0 times the length of the PVA film after the third stretching. Finally, the PVA film after the fourth stretching was immersed in an aqueous solution containing 3% by mass of potassium iodide for 15 seconds and then dried at 60° C. for 4 minutes to obtain a polarizing film. The polarizing brightness and color uniformity of the polarizing films obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were measured, and the measurement results are shown in Table 2.

[0056] Polarization brightness measurement method: overlap two identical polarizing films with the same orientation direction, and measure the transmittance (H0) at a wavelength. Overlap two identical polarizing films with perpendicular orientation directions, and measure the transmittance (H0) at a wavelength. 90 ), the partial brightness is calculated by the following formula: [(H0-H 90 ) / (H0+H 90 )] 1 / 2 .

[0057] Color uniformity measurement method: overlap two identical polarizing films in an orthogonal manner, illuminate one side with a light box with a light output of 14000lx, observe the color uniformity of the other side, and evaluate according to the following rules: O: no color unevenness, Δ: slight color unevenness, X: obvious color unevenness.

[0058] Table 1

[0059]

[0060] Table 2

[0061]

[0062]

[0063] (Table 2 continued)

[0064]

[0065] (O: no color unevenness, Δ: slight color unevenness, X: obvious color unevenness)

[0066] As shown in Table 2, the melting points (Tm) of the PVA films of Examples 1 to 4 are all >210°C, and the ΔTm at any two locations is <3.2°C. The polarizing films made using them have good color uniformity (no color unevenness). In contrast, the PVA films of Comparative Examples 1 to 3 have melting points (Tm) greater than 210°C, or ΔTm at any two locations greater than 3.2°C. The polarizing films made using them have poor color uniformity, with slight or obvious color unevenness. In particular, Comparative Examples 2 and 3 have crystallization temperatures (T c ) is greater than 153.5℃, the boron content is not 16 to 19ppm, or the standard deviation of the hysteresis is greater than 3nm, the color uniformity of the polarizing film is obviously poor (obvious color unevenness). Therefore, the melting point (Tm) of the PVA film in this case is greater than 210℃, and ΔTm at any two points is less than 3.2℃. When used to prepare polarizing films, it can have color uniformity and is not prone to color blocks and spots.

[0067] In summary, the PVA film of the present invention has a melting point (Tm) > 210°C, and ΔTm < 3.2°C at any two locations. It has color uniformity after stretching and dyeing, and does not produce color unevenness problems such as color blocks or spots. It effectively improves the defects of PVA film in manufacturing optical films and improves the yield of manufacturing optical films, especially large-size polarizing films.

[0068] The present invention has been described in detail above. The above is only a preferred embodiment of the present invention and should not be used to limit the scope of implementation of the present invention. That is, all equivalent changes and modifications made according to the scope of the patent application of the present invention should still fall within the scope of the patent of the present invention.

Claims

1. A PVA film, characterized in that: After being treated with 0.2 wt % boric acid aqueous solution, the melting point (T m )>210°C, and the melting point difference between any two points of the PVA film (ΔT m )<3.2℃.

2. The PVA film according to claim 1, characterized in that After being treated with 0.2 wt % boric acid aqueous solution, the crystallization temperature (T c )<153.5℃.

3. The PVA film according to claim 2, characterized in that: After being treated with 0.2 wt % boric acid aqueous solution, the crystallization temperature difference (ΔT c )<3.85℃.

4. The PVA film according to any one of claims 1 to 3, characterized in that: The standard deviation of hysteresis is <3nm.

5. The PVA film according to claim 4, characterized in that: 0.12 g of the PVA film was treated with a 0.2 wt % boric acid aqueous solution, and the boron content of the aqueous solution after being dissolved in water was 16 to 19 ppm.

6. An optical film, characterized in that: The invention is prepared from the PVA film as claimed in any one of claims 1 to 5.

7. The optical film according to claim 6, wherein: It is a polarizing film.

8. The optical film according to claim 7, wherein: The polarizing film has a polarization brightness>99.

8.

9. A method for manufacturing a PVA film according to any one of claims 1 to 4, characterized in that: It includes: (a) stirring a polyvinyl alcohol resin at a heating rate of 4 to 20° C. / hour, and maintaining the temperature for 2 to 4 hours after the dissolution temperature reaches 100° C., and reversing the stirring direction three times per hour to form a polyvinyl alcohol casting solution; (b) casting the casting solution onto a casting drum; and (c) forming the PVA film after drying; The drying in step (c) is carried out by a hot roller or a floating dryer, and the maximum / minimum air flow rate received by the film along the width direction in the floating dryer is ≤3.0; The drying is performed in a vehicle compartment, and the temperature difference between adjacent vehicle compartments is below 65°C.

10. The manufacturing method according to claim 9, characterized in that: The rotation speed of the casting drum is 3-7 m / min.

11. The manufacturing method according to any one of claims 9 to 10, characterized in that: The polyvinyl alcohol casting solution further includes a plasticizer, and the plasticizer is 3 to 30 parts by weight relative to 100 parts by weight of the polyvinyl alcohol-based resin.

12. The manufacturing method according to claim 11, characterized in that: In the polyvinyl alcohol casting solution, the content of the polyvinyl alcohol-based resin is 10 to 60% by weight.

13. The manufacturing method according to claim 12, characterized in that: The degree of polymerization of the polyvinyl alcohol-based resin is between 800 and 10,000.

Citation Information

Patent Citations

  • Polyvinyl alcohol film and method for producing the same

    JP2006188655A

  • Polyvinyl alcohol-based film, polarizing film using the same, polarizing plate, and manufacturing method for polyvinyl alcohol-based film

    JP2017102436A